Peran Kepala Sekolah Terhadap Kedisiplinan Guru di SMKNegeri 3 Halmahera Barat - Asnita Ode Samili; Ningsi Saibi; Fitriana Ibrahim; Syarifuddin Adjam; Jainudin Hasim (Peneliti.net, 2022)
Effective principals will certainly affect teacher performance, so teachers will be more enthusiastic in carrying out their duties and responsibilities as well as their obligations as teachers. This is because the teacher feels that he or she gets attention, security and recognition for his achievements. This study aims to determine the role of the principal on teacher discipline. The aspect studied is the principal's efforts in disciplining teachers at SMK Negeri 3 West Halmahera, the method used is a qualitative descriptive method. The subjects of this study were the principal and teachers. Data collection was carried out through observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The researcher uses source triangulation to obtain the validity of the data. The results obtained indicate that the principal has tried to discipline teachers at SMK 3 West Halmahera, these efforts include making regulations, teaching habits, giving sanctions punishments for teachers who violate, giving rewards and consistency, but in its implementation and implementation it has not been fully implemented. good